Tinjuan Yuridis Terhadap Pasal 28 Ayat (2) UU ITE (Sudi Kasus : I Gede Ari Astina Alias Jerinx atau JRX ) - Putera, Ryadh Mega (Universitas Merdeka Madiun, 2021)
Article 28 paragraph (2) of the ITE Law is one of the articles that regulate the spread of hatred in social media. The provisions of that article still lead to a multi-faceted understanding of the sense of hatred that the passage refers to. This study aims to find out about the regulation of hatred according to positive law and the arrangement of the article in the future. This study uses normative legal research methods that are sourced from the legislation. Hate-related arrangements are regulated in some legislation, but in particular, a sense of hatred in social media is set in Article 28 paragraph (2) of the ITE Law. The use of Article 28 the case of I Gede Ari Astina better known as Jerinx and also the difficulty in solving cases deemed to have violated this article. The provisions of the article still need improvement to further limit the actions of other users, while for Article 28 paragraph (2) there is no change.Â Keywords: Hatred; Article 28 paragraph (2; UU ITE.